Surgical cancellation rates due to perioperative hypertension: implementation of multidisciplinary guidelines across primary and secondary care - Soni,S; Shah,S; Chaggar,R; Saini,R; James,E; Elliot,J; Stephens,J; McCormack,T; Hartle,A (Anaesthesia, 2020)
Patients with uncontrolled hypertension are at increased risk of complications during general anaesthesia but the number of patients whose surgery is delayed or cancelled due to hypertension remains unknown. Prospective, regional multicentre service evaluations were performed on consecutive patients undergoing elective surgery before and after the publication of new guidelines from the Association of Anaesthetists and the British Hypertensive Society. The aim was to quantify the number of operations cancelled due to hypertension alone and to assess impact of the guidelines on cancellation rates. In October 2013 (before the publication of the guidelines), 1.37% (95%CI 0.69–2.11%) of patients listed for elective surgery were cancelled solely due to raised blood pressure. This reduced significantly to 0.54% (95%CI 0.20–0.92%, p < 0.001) in 2018. There was a significant reduction in inappropriate cancellations for stage 1 or 2 hypertension from 2013 to 2018 (72 vs. 14, respectively, p < 0.001) in keeping with the recommendations in the guidelines. Furthermore, the number of patients being referred back to primary care for the management of hypertension reduced from 2013 to 2018 (85 vs. 30, respectively, p < 0.001). Our data suggest achievement of three major outcomes: reduced surgical cancellations due to hypertension alone; improved detection of significant hypertension before elective surgery; and reduced referral back to primary care from hospital for hypertension management. To the best of our knowledge, this is the first time the successful implementation of guidelines from the Association of Anaesthetists has been assessed on such a broad scale. Our data indicate that these guidelines have been effectively implemented in both primary and secondary care, which is likely to have made a positive psychosocial, physical and economic impact on patients and the NHS.